2020
DOI: 10.1016/j.cherd.2020.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Asset maintenance optimisation approaches in the chemical and process industries – A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 186 publications
(252 reference statements)
0
7
0
2
Order By: Relevance
“…This provides valuable insight into the effectiveness of the system, allowing for further development and optimization. 25…”
Section: Management Systemmentioning
confidence: 99%
“…This provides valuable insight into the effectiveness of the system, allowing for further development and optimization. 25…”
Section: Management Systemmentioning
confidence: 99%
“…In order to maintain safe operation of high-pressure pipelines, appropriate maintenance optimisation strategies are required to maximise reliability. A number of such studies can be found in open literature (see for example Castanier and Rausand, 2006;Gong and Zhou, 2018;Chin et al, 2020). As part of future work, a combined approach involving pipeline maintenance optimisation strategies and the current ESDV multi-objective optimisation model would be extremely useful.…”
Section: Multi-objective Optimisation Studymentioning
confidence: 99%
“…Another potential benefit of using modular and parallel units is to enhance process reliability which indicates the probability of a system to perform its designated function over a specified time interval. While this topic is beyond the scope of the current paper, we refer the readers to the recent works 53,54 for more information.…”
Section: Operability and Control Challenges In Intensified And Modulamentioning
confidence: 99%